The role of early life nutrition in the determination of healthy ageing - Mohamed, Hamid Jan Jan (Indonesian Nutrition Association, 2024)
Nutrition plays an important role at all life stages—before and during pregnancy, lactation, infancy, and childhood, as well as during adult life. Maternal nutrition has a major impact on the infant, not only because the nutrient exchange through the placenta and breast milk is involved in fetal and infant growth, but it also plays a role in determining the offspring’s risk of developing non-communicable diseases (NCDs) during adulthood.